Effects of alcohol, rumination, and gender on the time course of negative affect. Issue 7 (3rd October 2017) - Simons, Jeffrey S.; Emery, Noah N.; Simons, Raluca M.; Wills, Thomas A.; Webb, Michael K.
ABSTRACT: This study modelled associations between gender, ruminative cognitive style, alcohol use, and the time course of negative affect over the course of 43, 111 random assessments in the natural environment. Participants ( N  =  263) completed 49 days of experience sampling over 1.3 years. The data indicated that rumination at baseline was positively associated with alcohol dependence symptoms at baseline as well as higher negative affect over the course of the study. Consistent with negative reinforcement models, drinking served to decrease the persistence of negative affect from moment to moment. However, this ameliorative effect of drinking was evident only among women, suggesting an increased risk for negative reinforcement driven drinking behaviour. In addition, rumination appeared to counteract the desired effects of alcohol on mood among women. This suggests that women who ruminate more may be motivated to consume larger amounts of alcohol to achieve the desired effects. Overall, the results indicate that ruminative cognitive style and the persistence of negative affect from moment to moment may reflect an individual vulnerability for the development of alcohol use disorder especially among women.